OP74 Measuring Sexual Behaviour Comes of Age: A Comparison of Outcomes in the 2010 Health Survey for England with the National Survey of Sexual Attitudes and Lifestyles. (17th September 2012) - Mercer, CH; Robinson, C; Craig, R; Nardone, A; Johnson, AM
Abstract : Background: The Health Survey for England (HSE) is a general health survey administered annually to a probability sample of people living in England. In 2010, the HSE included, for the first time, questions about sexual health, which previously were considered too sensitive for a general health survey. This paper compares the reporting of sexual behaviours by people aged 16–44 in HSE–2010 with data collected by the second British National Survey of Sexual Attitudes and Lifestyles (Natsal–2), Britain's most recent, dedicated national probability survey of sexual behaviour. Methods: In HSE–2010, 8, 420 people aged 16–69 were interviewed, of whom 2, 911 were aged 16–44. Natsal–2 interviewed 12, 110 people aged 16–44 in 1999/2001. HSE–2010 used pen-and-paper self-completion questionnaires for the sexual health questions, while Natsal–2 used computer-assisted personal-interviews including computer-assisted self-interview for the more sensitive questions, including those on sexual health. HSE–2010 used the same question wording developed and piloted for Natsal. Results: Collecting sexual behaviour data was acceptable to HSE–2010 participants with low item non-response (5–10%), albeit slightly higher than in Natsal–2 (<5%). Reported age at first heterosexual intercourse was comparable in the two surveys: median ages of 17 (men) and 16 (women) among those aged 16–24. However, for some very sensitive questions there were lower levels of reporting in HSE–2010 than in Natsal–2: while the proportion reporting same-sex in the last 5 years was similar (2–3%), reporting of ever having same-sex was lower in HSE–2010 for men (2% vs. 5% in Natsal–2). Similarly, the mean number of opposite-sex partners reported in HSE–2010 was a little lower than in Natsal–2, particularly among men: 9.5 vs. 12.7, respectively, in contrast to 5.4 vs. 6.5, respectively, among women. Men in HSE–2010 were also slightly less likely to report being diagnosed with sexually transmitted infection(s) than in Natsal–2: 8.7% vs. 11.1%, respectively; but this was reported by similar proportions of women: 12% in both surveys. Conclusion: The inclusion of questions on sexual behaviour in HSE–2010 has demonstrated the feasibility and utility of measuring sexual behaviour in general health surveys, albeit in less detail than in a survey focused on sexual behaviour such as Natsal. General health surveys such as the HSE provide a useful vehicle for monitoring sexual risk behaviour more frequently than is possible with decennial Natsal surveys. Health surveys should not shy away from also measuring sexual behaviour, especially in light of the associations between health status and sexual health outcomes of satisfaction, function and behaviour.